Exploring the boundaries of landscape architecture - Bell, Simon, 1957- 412385; Herlin, Ingrid Sarlov 520868; Stiles, Richard 520869 (New York, NY : Routledge, 2012)
"What insights can an anthropologist gain from the day-to-day use of parks? How does an economist view the supply and demand of an outdoor space? Why would an architect divide landscape into 'cultural' and 'natural' elements? Experts from around the world give their thoughts on how disciplines outside landscape architecture view the profession. Their insights link together theories from neighbouring areas, giving constructive feedback on the lessons they've gained from work in the environment and their contributions back to the subject"--